Effect of Gender-affirming Facial Feminization Surgery on Psychosocial Outcomes. Issue 5 (4th May 2023) - Caprini, Rachel M.; Oberoi, Michelle K.; Dejam, Dillon; Chan, Candace H.; Potemra, Hi'ilani M.K.; Morgan, Katarina B.J.; Weimer, Amy; Litwin, Mark S.; Mendelsohn, Abie H.; Lee, Justine C.
Abstract : Objective: This study investigates the effect of gender-affirming facial feminization surgery (FFS) on psychosocial outcomes in patients with gender dysphoria. Background: Comprehensive analyses of psychosocial outcomes after gender-affirming FFS are absent in the literature resulting in a paucity of information on the impact of FFS on quality of life as well as ramifications in health insurance coverage of FFS. Methods: Scores from 11 validated, quantitative instruments from the Patient-Reported Outcomes Measurement Information System (PROMIS) assessing anxiety, anger, depression, global mental health, global physical health, satisfaction with sex life, positive affect, emotional support, social isolation, companionship, and meaning and purpose. Patients within the preoperative group (pre-FFS) were evaluated >30 days before surgery and patients within the postoperative group (post-FFS) were evaluated ≥10 weeks after surgery. Results: A total of 169 patients [mean (SD) age, 33.5 (10.8) years] were included. Compared with the pre-FFS group (n=107), the post-FFS group (n=62) reported improved scores anxiety (56.8±8.8 vs 60.1±7.9, P =0.01), anger (47.4±7.6 vs 51.2±9.6, P =0.01), depression (52.2±9.2 vs 57.0±8.9, P =0.001), positive affect (46.6±8.9 vs 42.9±8.7, P =0.01), meaning and purpose (49.9±10.7 vs 46.2±10.5, P =0.03), global mental health (46.7±7.6 vs 43.1±9.2, P =0.01), and social isolation (52.2±7.5 vs 55.4±7.4, P =0.01). Multivariable analysis to account for the effects of other gender-affirming surgeries, hormone therapy duration, preexisting mental health diagnoses, socioeconomic disparities, and patient-reported quality of social relationships on psychosocial functioning demonstrated that completion of FFS was independently predictive of improved scores. Conclusions: Gender-affirming FFS improves the quality of life by multiple psychosocial domains in transfeminine patients.